Soursop Effect in Cervical Cancer Apoptosys Mechanism - Lelly Yuniarti; Herri S. Sastramihardja; Wida Purbaningsih; Maya Tejasari; Titik Respati; Enggar Hestu; Agly Adithya (Universitas Islam Bandung, 2014)
Cervical cancer is the fifth leading cancer cause of women death in Indonesia. Acetogenin, flavonoids, and tannins in sour sop leaves have anti-cancer effects through regulated genes which involved in apoptotic process such as in caspase-3. This study aimed to determine the effect of ethanol extract of sour sop leaves to apoptosis and caspase-3 gene expression in HeLa cell cultures. This was an in vitro study using HeLa cell culture samples divided into 4 groups in Laboratory of Biological Science Center Institute Technology Bandung. The first group was HeLa cell cultures without sour sop leaves ethanol extract. The 2nd,3rd, and 4th group were HeLa cells cultures which were given sour sop leaves ethanol extract with concentration of 60 μg/mL, 120 mg/mL, and 240 mg/mL respectivelly. Apoptosis in each group was examined using terminal deoxynucleotidyl transferase-mediated (TUNEL) method and the expression of the caspase 3 gene by reverse transciptase-polimerase chain reaction (RT-PCR). One way analysis of varians (ANOVA) with confidence level of 95% were used as statistical analysis. The result showed the effect of the sour sop leaves ethanol extract increased the apoptosis percentage in HeLa cells culture but did not affect the gene expression of caspase-3. EFEK DAUN SIRSAK DALAM MEKANISME APOPTOSIS KANKER SERVIKSKanker serviks adalah penyebab kematian kelima untuk wanita di Indonesia. Asetogenin, flavonoid, dan tanin dalam daun sirsak terbukti mempunyai pengaruh antikanker melalui regulasi gen melalui proses apoptosis seperti pada caspase-3. Penelitian ini bertujuan untuk menentukan efek ekstrak etanol daun sirsak untuk apoptosis dan ekspresi gen caspase-3 dalam kultur sel HeLa. Penelitian ini adalah penelitian in vitro menggunakan sel kultur HeLa yang dibagi menjadi 4 kelompok dilakukan di Laboratorium Biological Science Center Institut Tehnologi Bandung. Grup pertama adalah sel kultur HeLa tanpa ekstrak etanol daun sirsak sedangkan grup dua, tiga dan empat adalah sel kultur HeLa yang mendapat ekstraks etanol daun sirsak dengan konsentrasi 60 μg/mL, 120 mg/mL, dan 240 mg/mL secara berturut-turut. Apoptosis dalam setiap kelompok diperiksa dengan menggunakan metode terminal deoxynucleotidyl transferase-mediated (TUNEL) dan ekspresi gen caspase-3 dengan menggunakan reverse transciptase-polimerase chain reaction (RT-PCR). One way analysis of varians (ANOVA) dengan tingkat kepercayaan 95% digunakan untuk analisis statistik. Hasil penelitian menunjukkan bahwa ekstrak etanol daun sirsak meningkatkan persentase apoptosis dari kultur sel HeLa tetapi tidak berpengaruh pada ekspresi gen caspase-3.